What is the future of schooling? Resignifying the meaning of schools in the COVID-19 era - Pablo Rivera-Vargas; Universidad de Barcelona y Universidad Andrés Bello (Chile); Raquel Miño-Puigcercós; Universidad de Barcelona; Ezequiel Passerón; Universidad de Barcelona; Gustavo Herrera Urizar; Universidad Católica de Valparaiso (Escuela de Psicología, Pontificia Universidad Católica de Valparaíso, 2021)
As a result of the mandatory passage to distance education, the Covid-19 pandemic has led us, on the one hand, to revalue the role of schools, and on the other hand, to review its meaning and recognize the challenges that we will face once the pandemic is over. This article identifies the main problems that are guiding the debate about the meaning of the school experience in the covid era. Using a qualitative methodological approach based on co-design, 122 interviews with academic, school and institutional significant and relevant voices from different parts of the world were carried out. The article presents the results of the analysis of 21 interviews that were selected for their direct impact on the need to reflect and question the meaning of schools. As a result of this work, four dimensions of analysis and 40 emerging questions were generated on this issue. The preliminary results acknowledge the urgency to revalue the school as an educational, socializing and transforming institution, generating spaces for dialogue, care, critical literacy and exchange.